2013
DOI: 10.1115/1.4023127
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Properties of Couple-Stress Fluid Flow in an Asymmetric Channel With Peristalsis

Abstract: The heat transfer characteristics of a couple-stress fluid (CSF) in a two-dimensional asymmetric channel is analyzed. The channel asymmetry is produced by choosing the peristaltic wave train on the walls to have different amplitudes and phase. Mathematical modeling corresponding to the two-dimensional couple stress fluid is made. Analytical expressions for the axial velocity, stream function, heat transfer, and the axial pressure gradient are established using long wavelength assumption. Numerical computations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…In addition, De Vries et al [12] found that the myometrial contractions may occur in both symmetric and asymmetric directions. Therefore, a great effort was devoted to study the peristaltic flow of Newtonian and nonNewtonian fluids in an asymmetric channel [1323], and recently of Jeffrey and Johnson-Segalman fluids; see, for example, [2428]. …”
Section: Introductionmentioning
confidence: 99%
“…In addition, De Vries et al [12] found that the myometrial contractions may occur in both symmetric and asymmetric directions. Therefore, a great effort was devoted to study the peristaltic flow of Newtonian and nonNewtonian fluids in an asymmetric channel [1323], and recently of Jeffrey and Johnson-Segalman fluids; see, for example, [2428]. …”
Section: Introductionmentioning
confidence: 99%
“…Applying the boundary conditions (5) and (6) on the -equation given in (28) and (29), we obtain the following system …”
Section: The General Closed Form Solutionmentioning
confidence: 99%
“…22 Akbar and Nadeem 23 also discussed the peristaltic flow of chyme in small intestine by considering couple-stress fluid. Heat transfer analysis in two-dimensional peristaltic flow of couple-stress fluid through an asymmetric channel was conducted by elmaboud et al 24 The peristaltic flow induced by waves traveling along the walls involve elastic properties. Consideration of such wall properties like tension and damping are essential in various practical situations.…”
Section: Introductionmentioning
confidence: 99%